Laser-Assisted Fabrication of Materials - Majumdar, Jyotsna Dutta.; Manna, Indranil. (Springer Series in Materials Science, 2013)
Laser assisted fabrication involves shaping of materials using laser as a source of heat. It can be achieved by removal of materials (laser assisted cutting, drilling, etc.), deformation (bending, extrusion), joining (welding, soldering) and addition of materials (surface cladding or direct laser cladding). This book on þLaser assisted Fabrication<U+0019> is aimed at developing in-depth engineering concepts on various laser assisted macro and micro-fabrication techniques with the focus on application and a review of the engineering background of different micro/macro-fabrication techniques, thermal history of the treated zone and microstructural development and evolution of properties of the treated zone.